Desenvolvimento de framework para análise e simulação dinâmica de sistemas elétricos de potência - SENA, José Adolfo da Silva (Universidade Federal do Pará, 2013)
This thesis presents a flexible Object Oriented (OO) methodology for the design and implementation of simulation software system used to perform dynamic studies of large electrical power systems. The proposed OO methodology aims at make easier the development, upgrade and maintenance of complex software systems. The user's requirements are mapped to set base classes which are atomic classes to perform the modeling of the dynamic devices such as electrical generators. In order to evaluate the methodology, a simulation software system was developed using the OO modeling. In order to evaluate the Framework performance, two study cases were carried out. The first one apply the Framework on the modeling and simulation of generation units at Tucuruí Power Plant. The simulation results were comparated to data measurements from field tests and shown the good performance of the Framework on reproducing electromechanical phenomena of this large Power Plant. In the second study, by its turn, the Framework was applied to the modeling of a Photovoltaic (PV) generation system, along with its Maximum Power Tracking (MPPT). The MPPT control was implemented using digital techniques. The simulation results show the good performance of the Framework on modeling the current as well as MPPT control of PV generations systems.